The effect of temperature on creep behavior of wood-plastic composites. (May 2014) - Chang, Feng-Cheng; Lam, Frank; Kadla, John F
The creep properties of wood-plastic composites limit their application, particularly in temperature variations affecting long-term performance. In this study, the effect of temperature was studied based on dynamic mechanical analysis spectra and isochrones and a newly developed stress-temperature incorporated creep equation. According to the dynamic mechanical analysis spectra, the addition of a higher content of wood flour resulted in higher moduli, indicating increased stiffness and lower mechanical loss factor. According to the isochrones, the creep strain of wood-plastic composites increased with elevated temperatures and stresses at the same time point. Moreover, the strain increased almost linearly with increasing stress at lower temperatures but became nonlinear with elevated temperature. With these findings, a stress-temperature incorporated creep equation was developed based on short-term creep tests. This empirical equation incorporates the effect of temperature in a power law equation. Good agreement was observed between the equation and experimental results.